Paleobiogeography of the Cretaceous-Tertiary mass extinction in planktic foraminifera. - KELLER G.; ADATTE T.; STINNESBECK W.; KAROUI N.; ZAGHBIB TURKI D.; LUCIANI, Valeria (2002)
Paleobiogeographic patterns of the Cretaceous-Tertiary (K-T) mass extinction in planktonic foraminifera in Tunisia, spanning environments from open marine upper bathyal, to shelf and shallow marginal settings, indicate a surprisingly selective and environmentally mediated mass extinction. This selectivity is apparent in all of the environmental proxies used to evaluate the mass extinction, including species richness, ecological generalists, ecological specialists, surface and subsurface dwellers, whether based on the number of species or the relative percent abundances of species. The following conclusions can be reached for shallow to deep environments: about three quarters of the species disappeared at or near the K T boundary and only ecological generalists able to tolerate wide variations in temperature, nutrients, salinity and oxygen survived. Among the ecological generalists (heterohelicids, guembelitrids, hedbergellids and globigerinellids), only surface dwellers survived. Ecological generalists which largely consisted of two morphogroups of opportunistic biserial and triserial species also suffered selectively. Biserials thrived during the latest Maastrichtian in well stratified open marine settings and dramatically declined in relative abundances in the early Danian. Triserials thrived only in shallow marginal marine environments, or similarly stressed ecosystems, during the latest Maastrichtian, but dominated both open marine and restricted marginal settings in the early Danian. This highly selective mass extinction pattern reflects dramatic changes in temperature, salinity, oxygen and nutrients across the K-T boundary in the low latitude Tethys ocean which appear to be the result of both long-term environmental changes (e.g., climate, sea level, volcanism) and short-term effects (bolide impact). (C) 2002 Elsevier Science B.V. All rights reserved.